PERSPEKTIF SA’ID NURSI TENTANG MUNAFIK DALAM TAFSIR ISHARAT AL-I’JAZ FI MAZANI AL-IJAZ - Mubarok, Ghozi; Ernasari, Ernasari (Universitas Al-Amien Prenduan, 2019)
Alquran was handed down to mankind as a guide to deal with all the problems of life, as in Surah Al-Baqarah verses 1-20 there are three human characters, namely believers, infidels and hypocrites. The hypocritical character according to Allah Almighty is worse than paganism, however, most people still do not know the characters that are synonymous with hypocrisy compared to the character of believers and infidels. Similarly, the problems that hypocrites can cause. The problem raised in this research is to explain the hypocritical character and what problems can be caused by hypocrisy according to Sa'id Nursi in Surah al-Baqarah verses 8-20. This research carries mufassir and ulama known as Badi' Al-Zaman (keajaiaban zaman). His real name is Sa'id Nursi, nicknamed Badi' Al-Zaman because the power of memory and the greatness of knowledge can match the scholars of his time. To find out more about the character and problems caused by hypocrisy, researchers use a qualitative approach method with a type of library reseach approach, this literature research contains data or in the form of materials needed and is related to this research. These materials come from literature in the form of books, dictionaries, documents, journals, magazines, encyclopedias and so on. The nature of the research used in this study is descriptive analysis, where the researcher collects data first and then clarifies, analyzes and interprets so that it can provide solutions to problems. In data collection techniques, researchers use technical documentation and use content anaysis in analyzing the data that has been collected. The hypocritical characteristics at the beginning of Surah al-Baqarah verses 8-20 according to Sa'id Nursi's perspective have a variety of bad characters such as likes to deceive or lie, like to ruin and make chaos, make fun of believers, look at the fools of believers and like to play with the faith. Hypocritical characters are also humanitarian and religious problems such as breaking the ropes of silaturrahmi, social messing, enemies of Islamic internat and hypocritical diseases can be possessed by everyone, in the sense that hypocritical traits can affect anyone.